Influence ratio of water and oil phases of emulsions with starch on viscosity, density, particle size and muddy turbidity of system - Lugovska, Oksana; Sidor, Vasyl (My University, 2014)
For the study were prepared 5 samples of food emulsions with varying amounts of oil phase and a constant amount of stabilizer (starch) and 5 samples of food emulsions using different amounts of starch at a constant amount of oil phase.
Keywords: starch; emulsions; turbidity; viscosity; density; particle size; крохмаль; емульсії; каламутність; в'язкість; щільність; розмір часток; крахмал; эмульсии; мутность; вязкость; плотность; размер частиц; кафедра експертизи харчових продуктів